2018
DOI: 10.1371/journal.pone.0193113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical exercise programs on cognitive function in Parkinson’s disease patients: A systematic review of randomized controlled trials of the last 10 years

Abstract: BackgroundGiven the relative importance of cognitive impairment, there was considerable interest in identifying the cognitive profile of PD patients, in order to ensure specific and appropriate therapeutic interventions.PurposeTo determine the effects of physical exercise programs on cognitive function in PD patients, compared with the control group.Data sourcesMedline, Cochrane, Scopus, PEDro and Web of Science (last searched in September 2016).Study selectionRandomized clinical trials examining the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(125 citation statements)
references
References 88 publications
2
115
0
8
Order By: Relevance
“…In contrast, research on the efficacy of physical exercise in treatment of other brain disorders is still in its infancy and therefore not part of the standard care. Although several studies have investigated the effect of physical exercise in different chronic brain disorders such as Alzheimer's disease (AD) [17,18], multiple sclerosis (MS) [19][20][21], Parkinson's disease (PD) [22,23], Schizophrenia (Sz) [24,25] and unipolar depression (UD) [26][27][28], results and mainly recommendations for clinical practice have been highly diverse [29]. As a consequence, current evidence for efficacy of exercise therapy is still disputed and exercise is not part of the regular care offer for patients with aforementioned disorders in most countries.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, research on the efficacy of physical exercise in treatment of other brain disorders is still in its infancy and therefore not part of the standard care. Although several studies have investigated the effect of physical exercise in different chronic brain disorders such as Alzheimer's disease (AD) [17,18], multiple sclerosis (MS) [19][20][21], Parkinson's disease (PD) [22,23], Schizophrenia (Sz) [24,25] and unipolar depression (UD) [26][27][28], results and mainly recommendations for clinical practice have been highly diverse [29]. As a consequence, current evidence for efficacy of exercise therapy is still disputed and exercise is not part of the regular care offer for patients with aforementioned disorders in most countries.…”
Section: Introductionmentioning
confidence: 99%
“…36 Exercise-based cardiac rehabilitation is a cornerstone of the secondary prevention of cardiovascular diseases, 37 and physical exercise programs can be beneficial for cognitive function in PD. 38 Therefore, in clinical settings, it may be important to promote physical activity at early stages of disease.…”
Section: Discussionmentioning
confidence: 99%
“…34 WML was also suggested to underpin, at least to some extent, the antiparkinsonian treatment-resistant symptoms that develop during the course of PD, such as gait difficulties and postural instability. 38 Therefore, in clinical settings, it may be important to promote physical activity at early stages of disease. 36 Exercise-based cardiac rehabilitation is a cornerstone of the secondary prevention of cardiovascular diseases, 37 and physical exercise programs can be beneficial for cognitive function in PD.…”
Section: Whole Group (N = 64) No Falls or Near Falls (N = 29) Falls Amentioning
confidence: 99%
“…Treadmill and bicycle intervention can be used when performing against resistance [43][44][45]47]. Da Silva and her coworkers [48] suggest a long-term effect in nonmotor signs and symptoms of Parkinson's disease, especially in cognitive aspects, in individuals performing treadmill training, just as Ferreira and her coworkers [49] showed that resistance training was an effective intervention in the reduction of anxiety symptoms and improved the quality of life in this population.…”
Section: Resistance Training and Muscle Strengthmentioning
confidence: 99%
“…This approach can be used with or without a body-weight-support system, depending on the motor difficulties of the individual with Parkinson's disease. It may be related with improvement in motor signs like motor action, balance, and gait, although the evidence is not so strong [2,48].…”
Section: Aerobic Training: Treadmill Cycling Free Walking Dance Amentioning
confidence: 99%